SARS‐CoV‐2 viral load in nasopharyngeal swabs in the emergency department does not predict COVID‐19 severity and mortality. (5th February 2021) - Le Borgne, Pierrick; Solis, Morgane; Severac, François; Merdji, Hamid; Ruch, Yvon; Alamé Intern, Karine; Bayle, Eric; Hansmann, Yves; Bilbault, Pascal; Fafi‐Kremer, Samira; Meziani, Ferhat; ,
Abstract: Introduction: The ongoing COVID‐19 pandemic has led to devastating repercussions on health care systems worldwide. This viral infection has a broad clinical spectrum (ranging from influenza‐like disease, viral pneumonia, and hypoxemia to acute respiratory distress syndrome requiring prolonged intensive care unit stays). The prognostic impact of measuring viral load on nasopharyngeal swab specimens (by reverse transcriptase polymerase chain reaction [RT‐PCR]) is yet to be elucidated. Methods: Between March 3 and April 5, 2020, we conducted a retrospective study on a cohort of COVID‐19 patients (mild or severe disease) who were hospitalized after presenting to the emergency department (ED) and had at least one positive nasopharyngeal swab during their hospital stay. We led our study at the University Hospitals of Strasbourg in the Greater East region of France, one of the pandemic's epicenters in Europe. Results: We have collected samples from a cohort of 287 patients with a confirmed diagnosis of COVID‐19 who were included in our study. Nearly half of them (50.5%) presented a mild form of the disease, while the other half (49.5%) presented a severe form, requiring mechanical ventilation. Median (interquartile range) viral load on the initial upper respiratory swab at admission was 4.76 (3.29–6.06) log10 copies/reaction. When comparing survivors and nonsurvivors, this viral load measurement did not differ according to subgroups (p = 0.332). Additionally, we have found that respiratory viral load measurement was predictive of neither in‐hospital mortality (adjusted odds ratio [AOR] = 1.05, 95% confidence interval [CI] = 0.85 to 1.31, p = 0.637) nor disease severity (AOR = 0.88, 95% CI = 0.73 to 1.06, p = 0.167). Conclusion: Respiratory viral load measurement on the first nasopharyngeal swab (by RT‐PCR) during initial ED management is neither a predictor of severity nor a predictor of mortality in SARS‐CoV‐2 infection. Host response to this viral infection along with the extent of preexisting comorbidities might be more foretelling of disease severity than the virus itself.